Clinical, sinonasal, and long‐term smell and taste outcomes in mildly symptomatic COVID‐19 patients. Issue 7 (29th April 2021) - Tarifi, Amjed; Al Shdaifat, Amjad A.; Al‐Shudifat, Abdel‐Ellah M.; Azab, Mohammed; Ismail, Ja'far; Bashir, Rand; Amro, Aous; Altarifi, Ahmad; Khader, Yousef
Abstract: Introduction: Coronavirus 2019 disease (COVID‐19) has variable clinical, sinonasal, and smell/taste outcomes. Methods: Observational study was conducted at a tertiary hospital in Amman, Jordan. Demographic data, clinical presentation and smoking status were collected. Sinonasal symptoms, using Sino‐Nasal Outcome Test (SNOT‐22) Questionnaire, were evaluated. Smell/taste dysfunction was followed for three months. Results: Ninety‐Seven patients had satisfactory responses. Eighty‐six patients were symptomatic (41 at presentation, and 45 during admission). Among those patients, 59.3% had cough, 52.3% sore throat and 48.8% fever. The most common initial symptom was sore throat. Shortness of breath and smell/taste dysfunction were significantly higher in females. Surprisingly, shortness of breath was more common in non‐smokers. Smell/taste dysfunction affected 25.6% of patients, but was the first symptom in only one patient. Fourteen of 22 symptoms in SNOT‐22 had significant increase. The overall average of symptoms scores increased from 0.472 to 1.034, with smell/taste dysfunction to have the most increment. The latter symptom recovered completely in 81% and dysgeusia developed in 9.5% at three months, and it recovered completely in all patients at six months. Conclusion: Although COVID‐19 may produce severe lower airways disease, it has modest effect on nose and paranasal sinuses. Moreover, smell/taste dysfunction is a prominent symptom, but it usually recovers dramatically.